2022
DOI: 10.1186/s13063-022-06304-x
|View full text |Cite
|
Sign up to set email alerts
|

Trials using deferred consent in the emergency setting: a systematic review and narrative synthesis of stakeholders’ attitudes

Abstract: Background Patients with acute conditions often lack the capacity to provide informed consent, and narrow therapeutic windows mean there is no time to seek consent from surrogates prior to treatment being commenced. One method to enable the inclusion of this study population in emergency research is through recruitment without prior consent, often known as ‘deferred consent’. However, empirical studies have shown a large disparity in stakeholders’ opinions regarding this enrolment method. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 61 publications
(124 reference statements)
1
15
0
Order By: Relevance
“…(24) In the 8 years since, many more trials have employed deferral of consent, including as the exclusive method of enrollment, as in AcT,(34) SWIFT DIRECT, (25) ULTRA, (26) and others. (27) Despite its frequent use in recent stroke trials, trial protocols have not offered a standardized approach to justifying the use of deferral, meaning they have not explicitly stated why it was required. In their review, Feldman et al identified mentions of the presence of REB approval (as in HASTA, IST-3, SYNTHESIS-Expansion), of the need for rapid treatment (as in INSULINFARCT, PIL-FAST), of the right of patients to not have alteplase withheld (PHANTOM-S), and of the ability of medical professionals to provide surrogate consent (RIGHT).…”
Section: Recent Experiences With Deferral Of Consent In Stroke Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…(24) In the 8 years since, many more trials have employed deferral of consent, including as the exclusive method of enrollment, as in AcT,(34) SWIFT DIRECT, (25) ULTRA, (26) and others. (27) Despite its frequent use in recent stroke trials, trial protocols have not offered a standardized approach to justifying the use of deferral, meaning they have not explicitly stated why it was required. In their review, Feldman et al identified mentions of the presence of REB approval (as in HASTA, IST-3, SYNTHESIS-Expansion), of the need for rapid treatment (as in INSULINFARCT, PIL-FAST), of the right of patients to not have alteplase withheld (PHANTOM-S), and of the ability of medical professionals to provide surrogate consent (RIGHT).…”
Section: Recent Experiences With Deferral Of Consent In Stroke Trialsmentioning
confidence: 99%
“…25 In the 8 years since, many more trials have used deferral of consent, including as the exclusive method of enrollment, as in AcT, 19 Solitaire With the Intention for Thrombectomy Plus Intravenous tPA vs DIRECT Solitaire Stent-Retriever Thrombectomy in Acute Anterior Circulation Stroke (SWIFT-DIRECT), 26 Ultra Early Tranexamic Acid After Subarachnoid Hemorrhage (ULTRA), 27 and others. 28 Despite its frequent use in recent stroke trials, trial protocols have not offered a standardized approach to justifying the use of deferral, meaning they have not explicitly stated why it was required. In their review, Feldman et al 25 Advanced Unresectable or Metastatic Gastric or Gastroesophageal Junction (GEJ) Adenocarcinoma (SPOTLIGHT) made explicit statements of justification, citing the potential to increase enrollment and enable study participation for more severely affected patients.…”
Section: Recent Experiences With Deferral Of Consent In Stroke Trialsmentioning
confidence: 99%
“…An animation aimed at adults enrolled in emergency care research which describes RWPC was developed by another research team (CoMMiTED Study) [108]. Systematic reviews have explored stakeholders' views about the acceptability of RWPC [109], including ethnic minority populations' views [110]. Such studies have found that RWPC is generally acceptable to patients, families, and practitioners, but highlighted the importance of contextual factors.…”
Section: Current Research and Guidancementioning
confidence: 99%
“…The need for more guidance for RECs who are reviewing emergency and urgent care trials, and support for consent processes for patients and members of the public who join research teams and advise on studies, has also been highlighted [106,109,117].…”
Section: Future Researchmentioning
confidence: 99%
“…Since severe infections are emergencies, and treatment options for AMR pathogens are limited, deferred consent procedures may be also considered for these trials. 19 …”
Section: Informed Consentmentioning
confidence: 99%